Lexical peculiarities of advertising texts as a marker of cultural specificity - E. A. Miroshnikova (Гуманитарные и юридические исследования)
The article studies pragmatic and culturally significant lexical features of advertising texts of the tourism industry in Russian and English. The article raises such topical issues as identifying the linguistic and cultural specifics of the advertising text in English and Russian, increasing the pragmatic power of the advertising text using vocabulary with a cultural component, ways of translating lexical units unfamiliar to the reader, as well as pragmatically marked specific features of the vocabulary of tourist advertising texts in English and Russian. The article is based on the fact that lexical meanings connect the language with the way of life and the system of social relationships of the community speaking it, and the information received during the analysis of linguistic features is a source of identifying the linguistic and cultural specifics of the text.Special emphasis is placed on various types of realities as cultural signs widely used in tourist advertising communication. The analysis established the relationship between the lexical units used in advertising texts and the ethnocultural characteristics of the consumer of tourist advertising. In addition, the function of pragmatically significant linguistic means is studied, the features of the reproduction of non-equivalent vocabulary and words containing an ethno-cultural component of meaning are analyzed.The article does not ignore the fact that the main task of any advertising text is to increase the level of sales of the advertised product (in this article, of a tourist trip). Thus, the present study focuses on the pragmatic aspect of the advertising text and the impact of the lexicon on the perception of the advertising text.